Correlation Study Between Glycated Haemoglobin and Serum Zinc in People with Type 2 Diabetes - Rahman, Hasan Hafizur; Habibullah, Md; Israt, Shakila; Atiqullah, Syed; Fakhruzzaman, Mohammad; Al Aziz, Mohammad Zakaria; Safiullah, ABM (Journal of Medicine, 2026)
Type-2 Diabetes is the most common type form of diabetes, accounting for around 90% of all diabetescases. Diabetes affects zinc homeostasis in many ways; hyperglycemia,is responsible for the decrement oftotal body zinc level.The preponderance of evidence indicates that hyperglycemia increases the oxidativestress, may promote the generation of ROS by the activation of polyol and increased glucose autooxidation.The role of zinc in carbohydrate metabolism has already been a subject of considerable interest.Approximately 0.5% of crystalline insulin is zinc. Zinc deficiency in some studies has been associated withreduced insulin secretion and increased tissue resistance to insulin action.This analytical type of crosssectional study was carried out in the outdoor and indoor patients of Upazila health complex, Bhuapur,Tangail,Bangladesh,between the periods from January,2019 to 30th June,2019.A total of 140 subjects,age ranged from 35-65 years were included in this study.Among them 70 age matched type-2 diabetic patientswere taken as study group (Group II ) and 70 healthy subjects were taken as control group (Group I). Group I again subdivided into control group male (Group IA) and control Group female (Group IB). Group II also subdivided into study group male (Group IIA) and study group female (Group IIB). The results were calculated and analyzed by using SPSS software, laboratory analysis of HbA1c% by HPLC method, serum zinc by colorimetric method. In this study we found HbA1c, serum zinc is significant in study group in comparison with control HbA1c levels are significantly higher and scrum zinc levels significantly lower in the study group compared with controls group. In study group Mean(±SE) of serum zinc was decreased and the result was statistically highly significant (p<0.001) with 95% CI. Pearson’s correlation coefficient test of Serum zinc with HbA1c in type II DM found that there were a weak negative correlation male (r= -0.854) & female (r= - 0.838) between serum Zinc with HbA1c. So, patients with an higher HbA1c% were associated with a lower serum zinc level in study group population. Therefore, by this study we recommended that routine estimation of these parameters is important for prevention of complication related to type-2 diabetes for leading a healthy life . J MEDICINE 2026; 27(1): 16-20